HEAVY METAL ADSORPTION BY ARMENIAN NATURAL ZEOLITE FROM NATURAL AQUEOUS SOLUTIONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
Copper, zinc, chromium, mercury, manganese, arsenic, lead and cadmium removal from natural aqueous solutions by Armenian natural zeolites was examined by using batch type and dynamic type methods. The percentage of adsorption was determined for the adsorption system as a function of contact time and number of cycle. Two types of selective series of heavy metal ions have been carried out. According to the studies, the selectivity sequence can be given as Cu>Pb>Mn>Cd>Fe>Zn>Cr>Ni>As≥Hg and Cu>Pb>Cd>Zn>Fe≥Mn≥Ni≥As>Cr>Hg in dynamic type and batch type methods.
Keywords: heavy metals, natural zeolite, adsorption kinetics, selectivity